Exploratory phase of formulation of a social responsibility model for the Universidad Militar Nueva Granada - Espitia Cubillos, Anny Astrid; Quintero Rodríguez, Sergio Raúl (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
Natural resources exploitation has been an unstoppable process since industrialization, increasing in its wake factors such as environmental and social problems worldwide; taking this as a starting point, there is a global level, and especially in the productive sector, concern to improve this situation, and urgency to design and implement actions that promote sustainable development, through which integration is fostered the context with each of the organizations, and thus generate positive impacts on society both locally and globally. This situation also concerns educational institutions. To give an answer to this reality, the Universidad Militar Nueva Granada wants to formulate their model of social university responsibility, starting off with the revision of the actions of other higher public education institutions, that allows to identify the generated strategies and give answer to their propose of coaching professionals whit social responsibility and develop their missional functions under that same premise. For this purpose, progress was made at an economic, legal, ethical and discretional level documented and published by some of the Universities that make up the State University System (SUE) and compared with the current state of the University under study to have some references to serve as a starting point for the formulation of own University Social Responsibility.